PSV-1 Effects of Induction on Piglet Blood Parameters at Time of Farrowing - Mills, Kayla M (J Anim Sci, 2021)
Typically, sows are induced to farrow using prostaglandin followed by an injection of oxytocin 24 hours later. Benefits of induction can include decreased rate of stillbirths, dystocia, and postnatal mortality along with increasing the likelihood of farrowings being attended. Several studies have indicated that oxytocin administration may negatively impact fetal oxygen supply during parturition, potentially from umbilical cords breaking prior to birth, resulting in increased preweaning mortality. Therefore, the objective of this study was to determine if various induction protocols impact umbilical cord breakage and fetal blood parameters at birth. Fifty-eight primiparous and multiparous sows were assigned to one of three treatments: no induction (NO; n=24), or 2 cc Lutalyse administered on d114 of gestation followed by either 1 cc of oxytocin 24 hours later (OXY24; n=13) or 0.5 cc of oxytocin at 6 and 12 hours after Lutalyse (OXY6; n=21). Details of the farrowing process were recorded, and umbilical cord blood was collected from piglets at birth and evaluated on an iSTAT machine using an Abbott EC8+ test cartridge. There were no differences in total born, number born alive, stillborns, mummies, or assistance needed during farrowing. Sows in the OXY24 treatment tended to have longer farrowings when compared to both NO and OXY6 (5.6 vs 3.7 vs 3.7 hours; P=0.09). OXY24 gilts (38%) and NO sows (33%) tended to have more piglets born with broken umbilical cords than other parities and treatments (OXY24 sows: 19%; NO gilts: 18%; OXY6 gilts: 25%; OXY6 sows: 18%; P=0.07). Piglets born from NO sows had higher base excess, total carbon dioxide, and glucose which suggests that these piglets had prolonged moments of asphyxiation (P< 0.01). OXY24 piglets had the lowest blood pH which is indicative of hypoxic birthing conditions (P< 0.01). There were no signs of asphyxia in the blood parameters of piglets born from OXY6 sows. Therefore, multiple low doses of oxytocin to induce farrowing may be more beneficial for the welfare of the piglet during farrowing.